Endoplasmic reticulum stress sensitizes human esophageal cancer cell to radiation - Pang, Xue-Li (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate the role of endoplasmic reticulum (ER) stress in cancer radiotherapy and its molecular mechanism. METHODS: Tunicamycin (TM) was applied to induce ER stress in human esophageal cancer cell line EC109, and the radiosensitization effects were detected by acute cell death and clonogenic survival assay. Cell cycle arrest induced by TM was determined by flow cytometric analysis after the cellular DNA content was labeled with propidium iodide. Apoptosis of EC109 cells induced by TM was detected by annexin V staining and Western blotting of caspase-3 and its substrate poly ADP-ribose polymerase. Autophagic response was determined by acridine orange (AO) staining and Western blotting of microtubule-associated protein-1 light chain-3 (LC3) and autophagy related gene 5 (ATG5). In order to test the biological function of autophagy, specific inhibitor or Beclin-1 knockdown was used to inhibit autophagy, and its effect on cell apoptosis was thus detected. Additionally, involvement of the phosphatidylinositol-3 kinase (PI3K)/Akt/mammalian target of the rapamycin (mTOR) pathway was also detected by Western blotting. Finally, male nude mice inoculated subcutaneously with EC109 cells were used to confirm cell model observations. RESULTS: Our results showed that TM treatment enhanced cell death and reduced the colony survival fraction induced by ionizing radiation (IR), which suggested an obvious radiosensitization effect of TM. Moreover, TM and IR combination treatment led to a significant increase of G2/M phase and apoptotic cells, compared with IR alone. We also observed an increase of AO positive cells, and the protein level of LC3-II and ATG5 was induced by TM treatment, which suggested an autophagic response in EC109 cells. However, inhibition of autophagy by using a chemical inhibitor or Beclin-1 silencing led to increased cell apoptosis and decreased cell viability, which suggested a cytoprotective role of autophagy in stressed EC109 cells. Furthermore, TM treatment also activated mTORC1, and in turn reduced Akt phosphorylation, which suggested the PI3K/Akt/mTOR signal pathway was involved in the TM-induced autophagic response in EC109 cells. Tumor xenograft results also showed synergistic retarded tumor growth by TM treatment and IR, as well as the involvement of the PI3K/Akt/mTOR pathway. CONCLUSION: Our data showed that TM treatment sensitized human esophageal cancer cells to radiation via apoptosis and autophagy both in vitro and in vivo.